Willingness to Pay for Carbon Mitigation: Field Evidence from the Market for Carbon Offsets - Matthias Rodemeier (Institute of Labor Economics (IZA), 2023)
What do markets for voluntary climate protection imply about people's valuations of en- vironmental protection? I study this question in a large-scale field experiment (N=255,000) with a delivery service, where customers are offered carbon offsets that compensate for emissions. To estimate demand for carbon mitigation, I randomize whether the delivery service subsidizes the price of the offset or matches the offset's impact on carbon mitigation. I find that consumers are price-elastic but fully impact-inelastic. This would imply that consumers buy offsets but their willingness to pay (WTP) for the carbon it mitigates is zero. However, I show that consumers can be made sensitive to impact through a simple information treatment that increases the salience of subsidies and matches. Salient information increases average WTP for carbon mitigation from zero to 16 EUR/tCO2. Two complementary surveys reveal that consumers have a limited comprehension of the carbon-mitigating attribute of offsets and, as a result, appear indifferent to impact variations in the absence of information. Finally, I show that the widely-used contingent valuation approach poorly captures revealed preferences: Average hypothetical WTP in a survey is 200 EUR/tCO2, i.e., 1,150% above the revealed preference estimate.
Keywords: D61; D82; H21; Q51; Q58; 330; climate change; carbon mitigation; willingness to pay; carbon offsets; contingent valuation; nudging